MUSIC IN KHUN CHANG KHUN PHAEN LITERATURE BY VAJIRAYANA LIBRARY VERSION - Klangprasri, Sanong (Mahidol Music Journal, 2023)
This article presents the music that appears in the Sepha Ballad book of “Khun Chang Khun Phaen” (Vajirayana Library edition/Revised edition). It is intended for Thai musicians to have a better understanding of the essence of the music in Khun Chang Khun Phaen from the perspectives of a Thai musical historian and provides music content for academic reference. The article’s contents consist of: (1) the essence of reciting a Thai musicali verse; (2) the musical songs of Khun Chang Khun Phaen. The study found that, originally, Khun Chang Khun Phaen is a Thai folk tale based on the annals of the Ayutthaya period which is later called “Sepha” by the officials. Krom Phra Surasawadi recited it into a fairy tale story that was sung along with the rhythm of “Krap Khu” (Both hands playing a pair of wooden sticks). This became a pattern of reciting “Sepha ballad,” after which several episodes of Khun Chang Khun Phaen were added. During the reign of King Buddhalertla Naphalai (King Rama II), the story of Khun Chang Khun Phaen was recited with the Pipat ensemble. This marked the Formation of “Pipat Sepha Ballad Band” and the popularization of singing the verse to the melody, as evident in the total of 73 lyrics/songs in the Vajirayana Library edition. Furthermore, in each episode, there are other musical contents which can be used as a reference to expanding the perspective of Thai music to be broad and more profound.